Escitalopram maintenance treatment for prevention of recurrent depression: A randomized, placebo-controlled trial - Kornstein, Susan G.; Bose, Anjana; Li, Dayong; Saikali, Khalil; Gandhi, Chetan (The Journal of Clinical Psychiatry, 2006)
Background: Major depressive disorder is a recurrent illness that often requires maintenance antidepressant treatment. Escitalopram is a selective serotonin reuptake inhibitor (SSRI) that has shown efficacy in both acute and continuation treatment of major depressive disorder. The current trial examined the efficacy of maintenance escitalopram treatment in preventing depression recurrence in patients who responded to acute SSRI therapy. Method: Patients with recurrent DSM-IV defined major depressive disorder (≥2 previous episodes; baseline Montgomery-Asberg Depression Rating Scale [MADRS] score≥22) who had responded (MADRS score≤12) to acute open-label treatment (8 weeks) with 1 of 4 SSRIs (fluoxetine, sertraline, paroxetine, or citalopram) received open-label, flexible-dose continuation treatment (16 weeks) with escitalopram (10-20 mg/day). At the end of continuation treatment, patients maintaining response criteria were randomly assigned to 52 weeks of double-blind, fixed-dose maintenance treatment with escitalopram (10 or 20 mg/day) or placebo. Recurrence was defined as a MADRS score≥22 or insufficient therapeutic response during the double-blind phase. The study was conducted between October 16, 2000, and February 4, 2003. Results: A total of 234 patients who responded to acute open-label treatment with 1 of 4 SSRIs received at least 1 dose of open-label escitalopram continuation treatment. Of 164 patients who completed escitalopram continuation treatment, 139 were randomly assigned to doubleblind maintenance treatment with escitalopram (N=73) or placebo (N=66). Mean baseline MADRS scores at the start of the maintenance phase were<5 for both the placebo- and escitalopram-treatment groups. Time to recurrence was significantly longer in patients who received maintenance treatment with escitalopram compared with patients switched to placebo (hazard ratio=0.26, 95% CI=0.13 to 0.52, p<.001). Long-term escitalopram treatment was well tolerated. Conclusion: Maintenance treatment with escitalopram was well tolerated and significantly reduced the risk for recurrence of depression. Patients with few residual symptoms following continuation treatment with escitalopram experienced a high rate of depression recurrence when switched to placebo, demonstrating the need for maintenance therapy of recurrent major depressive disorder beyond 4 to 6 months of initial symptom resolution even if few residual symptoms are present. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: Adult; Aged; Aged, 80 and over; Citalopram; Depressive Disorder, Major; Double-Blind Method; Drug Therapy; Female; Humans; Maintenance Therapy; Male; Middle Aged; Recurrent Depression; Relapse Prevention; Secondary Prevention; Serotonin Reuptake Inhibitors; Serotonin Uptake Inhibitors; Treatment Effectiveness Evaluation; Treatment Outcome; drug therapy; escitalopram; maintenance treatment; recurrent depression; relapse prevention; selective serotonin reuptake inhibitor; treatment effectiveness